Developing Syllabus of Introduction to Literature for Students of English Department in Untirta - Eri Rahmawati; Ika Handayani; Siti Aisah; Delsa Miranty; Sri Widiastuti (English Department - University of Sultan Ageng Tirtayasa, 2017)
This research was conducted to seek the compatibility between the syllabus of Introduction to Literature Subject in English Department of UNTIRTA with the need of English Department students of UNTIRTA. The aims of this research are: 1) To find out what kind of English literature materials that English Department students need nowadays; 2) To find out the materials of English literature in the syllabus of Introduction to Literature; 3) To find out the kind of English literature syllabus needed by students of English Department in UNTIRTA. The objects of the research are limited to the syllabus of Introduction to Literature in English Department and the students of English Department in UNTIRTA. The theories used here are the theories of literature, curriculum implementation through syllabus and need analysis. This study is a qualitative research, a design and development program on English literature syllabus. This study is carried out in the undergraduate English Department of the Faculty of Teacher Training and Education in UNTIRTA. To ensure the validity and reliability of the results, the data were collected through the documentation of Introduction to Literature syllabus, the syllabus design and development, and the expert’s evaluation. The data from Introduction to Literature syllabus was analyzed to compare and relate it to the results of the needs analysis. Eventually, the evaluated syllabus was improved and reconstructed. Keywords: introduction to literature, syllabus design, need analysis